Security issues in the service oriented architecture web services security products are ready for prime time. - Pulier, Eric
Who doesn't love the service-oriented architecture (SOA)? You get efficiency in your application development, revolutionary ability to interoperate with partners and suppliers and mastery over change management that was never before possible.